Effect of the Active Cycle of Breathing Technique on Perioperative Outcome in Individuals With Esophagectomy: A Quasi-Experimental Study - Zhang, Si-Wen; Wu, Lei-Lei; Yang, Hong; Li, Chuan-Zhen; Wei, Wei-Jin; Wang, Min; Ma, Guo-Wei; Zhong, Jiu-Di (Frontiers in Surgery, 2021)
Background: The effect of active cycle of breathing technique (ACBT) on EC patients has not been well elucidated. In this research, we aim to explore the effect of ACBT on the perioperative outcomes in patients with esophageal carcinoma who underwent esophagectomy. Methods: Patients who underwent esophagectomy in an academic institution from December 2017 to July 2019 were included in this study. In a quasi-experimental study, participants were randomly divided into an experimental group (active cycle of breathing technique, n = 107) and an observational group (n = 106) by drawing lots. The chi-squared test, Cochran–Mantel–Haenszel test, Logistic regression analysis, and Kruskal–Wallis test were used to analyze data. A two-sided P value < 0.05 was considered statistically significant. The primary observational endpoint was the mean weight of the sputum. Other outcomes included the 6-minutes-walk test (6MWT), Borg scale, anastomotic leakage, and the length of hospital stay. Results: 95 patients underwent minimally invasive surgery, and 118 patients received open surgery. There were 16 patients with anastomotic leakage in the present study, and we found that patients in the observational group had higher odds of anastomotic leakage. The results showed that the mean weight of the sputum in the observation group was lighter than that of the experimental group. After esophagectomy, the experimental group had better outcomes than the observation group (Borg scale: 2.448 vs. 1.547; 6-MWT: 372.811 vs. 425.355m, all P < 0.05). The mean length of hospital stay was longer in the observation group (17.953 days) than that in the experimental group (12.037 days, P = 0.01). We also found that the observational group had a higher discharge ratio over 2 weeks in all cohort (adjusted OR 2.487, 95% confidence intervals 1.147-5.392, P = 0.021). Conclusion: Active cycle of breathing technique may improve the perioperative outcomes and decrease the length of hospital stay after surgery in patients with esophageal cancer. However, we need more researches to validate these findings.